Polymeric micelles for potentiated antiulcer and anticancer activities of naringin - Mohamed EA (Dove Medical Press, 2018)
Elham Abdelmonem Mohamed,1 Irhan Ibrahim Abu Hashim,1 Rehab Mohammad Yusif,1,2 Ahmed Abdel Aziz Shaaban,3 Ahmed Ramadan El-Sheakh,3 Mohammed Fawzy Hamed,4 Farid Abd Elreheem Badria5 1Department of Pharmaceutics, Faculty of Pharmacy, Mansoura University, Mansoura, Egypt; 2Department of Pharmaceutics and Pharmaceutical Technology, College of Pharmacy, Taibah University, Al-Madinah Al-Munawarah, Saudi Arabia; 3Department of Pharmacology and Toxicology, Faculty of Pharmacy, Mansoura University, Mansoura, Egypt; 4Department of Pathology, Faculty of Veterinary Medicine, Mansoura University, Mansoura, Egypt; 5Department of Pharmacognosy, Faculty of Pharmacy, Mansoura University, Mansoura, Egypt Abstract: Naringin is one of the most interesting phytopharmaceuticals that has been widely investigated for various biological actions. Yet, its low water solubility, limited permeability, and suboptimal bioavailability limited its use. Therefore, in this study, polymeric micelles of naringin based on pluronic F68 (PF68) were developed, fully characterized, and optimized. The optimized formula was investigated regarding in vitro release, storage stability, and in vitro cytotoxicity vs different cell lines. Also, cytoprotection against ethanol-induced ulcer in rats and antitumor activity against Ehrlich ascites carcinoma in mice were investigated. Nanoscopic and nearly spherical 1:50 micelles with the mean diameter of 74.80±6.56 nm and narrow size distribution were obtained. These micelles showed the highest entrapment efficiency (EE%; 96.14±2.29). The micelles exhibited prolonged release up to 48 vs 10 h for free naringin. The stability of micelles was confirmed by insignificant changes in drug entrapment, particle size, and retention (%) (91.99±3.24). At lower dose than free naringin, effective cytoprotection of 1:50 micelles against ethanol-induced ulcer in rat model has been indicated by significant reduction in mucosal damage, gastric level of malondialdehyde, gastric expression of tumor necrosis factor-alpha, caspase-3, nuclear factor kappa-light-chain-enhancer of activated B cells, and interleukin-6 with the elevation of gastric reduced glutathione and superoxide dismutase when compared with the positive control group. As well, these micelles provoked pronounced antitumor activity assessed by potentiated in vitro cytotoxicity particularly against colorectal carcinoma cells and tumor growth inhibition when compared with free naringin. In conclusion, 1:50 naringin–PF68 micelles can be represented as a potential stable nanodrug delivery system with prolonged release and enhanced antiulcer as well as antitumor activities. Keywords: naringin, pluronic F68, polymeric micelles, in vitro cytotoxicity, antiulcer, antitumor activity